RASIO LEGIS PENGATURAN USIA PERKAWINAN MENURUT UNDANG UNDANG PERKAWINAN DARI SUDUT PANDANG HUKUM NORMATIF - Berton Armandes Pakpahan (Yayasan Baitul Hikmah al-Zain, 2024)
Marriage is a bond between two human beings in their lives which is very important. Once the importance of marriage, it is not surprising that the world's religions regulate marriage, even the customs of society and state institutions do not lag behind regulating the marriage that prevails among the people. The law regulates marriages, one of which is the minimum age of marriage contained in article 7 paragraph (1) which states that,